The importance of the Nutritionist in promoting the health of individuals with insulin resistance (Research, Society and Development, 2023)
Insulin resistance leads to a greater need for circulating insulin to carry out its functions and effects, requiring special attention from healthcare professionals. This work sought to contribute to reflections on nutritional and non-pharmacological care for insulin resistance, emphasizing the role of the professional nutritionist in promoting the health of individuals with insulin resistance. This is a literature review, with research in databases such as Virtual Health Library and PubMed, analyzing sources from the last 5 years, complemented by official studies from the Ministry of Health, the Federal Council of Nutritionists and the Brazilian Association for the Study of Obesity and Metabolic Syndrome. The role of healthy lifestyle habits has been observed, as effective non-pharmacological treatments for insulin resistance, with emphasis on regular physical activity and exercise, reducing body weight, behavioral therapy, good diet and nutrition. The professional nutritionist plays a fundamentally important role in encouraging, establishing and strengthening these habits. Finally, the need and importance of implementing and strengthening interdisciplinary actions aimed at primary care and health promotion actions are highlighted in order to minimize complications related to insulin resistance.